(untitled) (Revista de Crítica Literaria Latinoamericana, 2013)
In this essay, the author examines the parallelisms between the poetry of the Pernambucan poet João Cabral de Melo Neto (1920-1999), and the democratic-pedagogical wave in Brazilian society during the 1960s. In Cabral’s poetry, there abound poems in which nature is connected to pedagogical and socio-racial concerns. More than a device of the poetic voice, nature is one of the great resources that enabled socio-economic hierarchies in Brazilian society since the colonial period. The didactic exchange between the mar and the sugar cane plantation is analyzed in the poems "O mar e o canavial" and" "O canavial e o mar", from the book of poems, A educação pela pedra (1962-1965), and as a counterpoint, the anti-didacticism of the poem "A educação pela pedra". Moreover, the socio-economic connection between the land Pernambuco and blacks is discussed in the poem "Paisagem do Capibaribe" from the book of poems, O cão sem plumas (1949-1950).